Microscopia de força elétrica em amostra de óxido de grafeno - Silva, José Júnior Alves da (2013)
Carbon-based structures have played a major role in scientific and technological fields. This is due to the versatility of the element carbon, the pillar of organic chemistry, which can form a variety of structures (about 10 million compounds), besides being a basic constituent of all known life forms. Depending on the conditions, this phenomenal element can occur in several allotropic forms: from an extremely brittle material, such as graphite, so incredibly resistant materials such as diamond, carbon nanotubes and graphene. These graphitic materials have been studied extensively, and present unique properties and great potential for technological applications. Among these materials, graphene currently occupies the most prominent position by having special electronic and mechanical properties. The graphene oxide is a class of graphitic structure consisting essentially of a graphene layer decorated with epoxide and hydroxyl groups on the surface and carboxyl and carbonyl groups on the edges. Its stoichiometry depends strongly on the method of production. In addition the graphene oxide is one of the main routes for obtaining large-scale graphene also it has several interesting properties, which allow, for example, biological applications, since their functional groups make it very reactive, besides being easily dispersed in water. Many issues related to graphene oxide are yet unclear, as also its structure, training procedure and mechanisms of interaction. Thus, the electric force microscopy (EFM) was used as the main tool to study electrostatic properties of a graphene oxide sample obtained by a modified Hummer method. By means of a simplified model, it was possible to develop a method for the analysis of the EFM measurements and so determine the presence and the sign of the net charge of the sample. Furthermore it is possible to clarify the origin of the edge phenomenon observed in EFM experiments.